Postherpes simplex encephalitis: a case series of viral-triggered autoimmunity, synaptic autoantibodies and response to therapy. (19th April 2018) - Alexopoulos, Harry; Akrivou, Sofia; Mastroyanni, Sotiria; Antonopoulou, Maria; Dinopoulos, Argirios; Giorgi, Melpo; Konstantinou, Kostas; Kouremenos, Evangelos; Lariou, Maria; Naoumis, Dimitrios; Pavlidou, Efterpi; Pavlou, Evaggelos; et al.
Background: Recent evidence suggests that patients with herpes simplex virus (HSV) encephalitis may relapse because of autoimmunity against the N-methyl-D-aspartate receptor (NMDAR). We present a case series of post-HSV relapsing encephalopathy associated with antibodies to central nervous system (CNS) synaptic antigens. Patient/Methods: Sera and cerebrospinal fluid (CSF) from five patients with HSV encephalitis who relapsed after antiviral therapy were tested for anti-NMDAR, gamma-aminobutyric acid b receptor (GABAbR), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR), Leucine-rich, glioma inactivated 1 (LGI1), anti -contactin-associated protein-like 2 (CASPR2) and dipeptidyl-peptidase-like protein-6 (DDPX) antibodies using cell-based assays. Results: Five patients (two infants, one child and two adults) developed post-HSV autoimmune encephalitis. The infants, aged 9 months and 10 months, after prompt and seemingly successful anti-HSV therapy, were readmitted with typical signs of NMDAR-encephalitis evolving within days, with NMDAR antibodies detected in both serum and CSF. Although they were promptly treated with intravenous immunoglobulin (IVIg) and with IVIg followed by rituximab, respectively, they were both left with psychomotor deficits. A 14-year-old girl with seizures due to HSV encephalitis improved with anti-HSV therapy. Later, she manifested intractable seizures and she was found positive for anti-NMDAR antibodies which persist. The two adults were women, aged 58 and 33 years. The first recovered after anti-HSV therapy and remained asymptomatic for 6 months, until she developed generalized seizures with persisting CSF anti-NMDAR antibodies; the second, who continued to be encephalopathic after 2 weeks of anti-HSV therapy, tested positive for anti-NMDAR antibodies in the serum and anti-GABAbR antibodies in the serum and CSF. She recovered fully following IVIg therapy but her serum anti-GABAbR antibodies persist 34 months later. Discussion: Infection of the CNS with HSV can trigger CNS autoimmunity associated not only with anti-NMDAR but also with anti-GABAbR antibodies. These antibodies can persist in the serum, even without associated symptoms, but their presence in the CSF is firmly associated with disease development. In contrast to children and adults who responded well to therapies, the infants had an incomplete recovery with severe psychomotor deficits probably due to the interference of anti-NMDAR antibodies with neuro-developmental processes.